Annotated translation of the documentary : "La herencia de Odebrecht Parte 1" produced by Ecuavisa, - Díaz Kang, Mario Abdul (2019)
The present research project aims to offer a contribution to the Ecuadorian subtitling and audiovisual industry through the rendering of the English subtitles for the Visión 360 documentary “La herencia de Odebrecht Parte 1” produced by Ecuavisa. This documentary was selected among a wide range of possibilities for its political and informative nature. The information it presents is only available in Spanish despite its international relevance; therefore, in consultation with Ecuavisa, the pertinent authorization was arranged and granted for an academic interlinguistic transfer of the contents. The rendering process was carried out considering the linguistic and technical parameters, as well as the constraints related to this type of translation. All the aforementioned elements have been analyzed along with the translator’s choices and strategies used to accurately convey the message of the source text.